Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/molecules28104121
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Phytochemical-Rich Citrus maxima Albedo Extract Using Response Surface Methodology

Woorawee Inthachat,
Piya Temviriyanukul,
Nattira On-Nom
et al.

Abstract: In the present study, response surface methodology (RSM) and Box–Behnken design (BBD) were employed to optimize the conditions for the extraction of C. maxima albedo from agricultural waste, to obtain notable phytochemicals. Ethanol concentration, extraction temperature, and extraction time were included as key factors contributing to the extraction. The results showed that the optimum extraction condition for C. maxima albedo was 50% (v/v) aqueous ethanol at 30 °C for 4 h, which provided total phenolic conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Thus, the extraction efficiency is dependent on the selection of the optimal solvent, temperatures, and mechanical agitation for use in the extraction process [ 34 ]. However, it has been reported that the use of mixed solvents, e.g., water-ethanol can extract more bioactive compounds than pure solvents [ 20 , 35 , 36 ]. However, reducing the solvent volume through reuse can be difficult when using mixed solvents, especially in small and medium industries.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the extraction efficiency is dependent on the selection of the optimal solvent, temperatures, and mechanical agitation for use in the extraction process [ 34 ]. However, it has been reported that the use of mixed solvents, e.g., water-ethanol can extract more bioactive compounds than pure solvents [ 20 , 35 , 36 ]. However, reducing the solvent volume through reuse can be difficult when using mixed solvents, especially in small and medium industries.…”
Section: Resultsmentioning
confidence: 99%
“…The number of revertant colonies per plate was counted. The MR was calculated from the average of the revertant number divided by the average of negative control revertant number [ 59 , 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…471 (Ames test) [ 27 ]. CHP (10–2000 µg/plate) was incubated with Salmonella typhimurium , including TA 98, TA100, TA102, TA1535, and TA1537, in the presence or absence of S9 extract [ 28 ]. The S9 extract (Sigma-Aldrich, St. Louis, MO, USA) was used to detect indirect-acting mutagens.…”
Section: Methodsmentioning
confidence: 99%